Synergetic process of condensing heat exchanger and absorption heat pump for waste heat and water recovery from flue gas. (1st March 2020) - Wang, Xiang; Zhuo, Jiankun; Liu, Jianmin; Li, Shuiqing
Highlights: A process is proposed to cool the high-humidity flue gas in coal-fired plants. This method can recover water from high-humidity flue gas. The waste heat in both the flue gas and the condenser cooling water are recovered. The system owns good economic with a short payback period. Abstract: This paper presents a process for recovering waste heat and water from high-humidity flue gas after the wet flue gas desulfurization scrubber. A condensing heat exchanger and an absorption heat pump are integrated into the condenser cooling water system by using a portion of the condenser cooling water as the working fluid. Two different arrangements of a reference power plant (1000 MW) are studied for the heating and non-heating seasons. The condensing heat exchanger performances in terms of heat transfer surface area, working fluid flow rate and heat transfer rate are evaluated, the influence of the coal type on them is specially examined. Besides, a technical-economic analysis of the process is also performed. The results indicate that the optimal logarithmic mean temperature difference range of the condensing heat exchanger is 15–30 °C considering the cost of heat transfer surface areas. The presented process is used to determine the best low-temperature working fluid for the condensing heat exchanger while the cooling tower efficiency and water balance are not affected. For bituminous coal, reducing the high-humidity flue gas temperature by 5 °C, 81.4 t/h of water is recovered and 44.8% of water consumption in the scrubber can be saved. During the heating season, 125.8 MW of waste heat is recovered with 50.3% from the condenser cooling water and 49.7% from the high-humidity flue gas. During the non-heating season, 77.9 MW of waste heat is recovered with all from the condenser cooling water. This process is economic, especially for burning high water content coal.